IDENTIFIKASI FAMILY POHON PENGHASIL BUAH YANG DI MANFAATKAN MASYARAKAT DI HUTAN TEMBAWANG - Wulandari, Mutiara; Manurung, Togar Fernando (Universitas Tanjungpura, 2018)
The Forest has biological diversity resources, Many of them also has potential to develop become an economic resources. Forest as ecosystem not only provide its natural resources in the kind of timbers, but also a lot of potential in non-timber forest products (NTFP), One of the example is fruit-producing trees that have been developed by the community to gathering food in people’s daily need. Tembawang forest is one of the example that can gives effort to preserve its natural diversity benfits. The purpose of this research are to recognize the types of fruit-producing trees and its morphology in tembawang forest, in empiyang village, jangkang district, sanggau regency. This research was conducted for 3 weeks in the forest of tembawang empiyang village. The researcher use exploration method, to recognizing all types of fruit-producing trees that found on the field, and took some samples by data collection techniques using primary data and secondary data. The data that had been collected, then analyzed and presented by descriptive qualitative. Based on the results of field observations, it found as many as 24 trees’ species belonging to 13 families, in the village forest tembawang empiyang village district jangkang sanggau. This case shows that tembawang forest, empiyang village jangkang sub-district, in sanggau regency has a high diversity in varieties of fruit-producing trees species.Keywords: Fruit Producers, Tembawang Forest, Trees Family